The Effect of Nanomaterials on the Properties of Limestone Dust Green Concrete - Alsaedy, S. M.; Aljalawi, N. (Engineering, Technology & Applied Science Research, 2021)
Portland cement is considered the most involved product in environmental pollution. It is responsible for about 10% of global CO2 emissions [1]. Limestone dust is a by-product of limestone plants and it is produced in thousands of tons annually as waste material. To fulfill sustainability requirements, concrete production is recommended to reduce Portland cement usage with the use of alternative or waste materials. The production of sustainable high strength concrete by using nanomaterials is one of the aims of this study. Limestone dust in 12, 16, and 20% by weight of cement replaced cement in this study. The study was divided into two parts: the first was devoted to the investigation of the best percentage of replacement of waste lime. The second part of the study evaluated the performance of concrete when adding nanomaterials. Three percentages of cement replacement 0.5%, 1%, and 1.5% with nano-Al2O3 were used. The most efficient content of hydrated lime used in this study which achieves sustainability and maintains the quality of concrete was (16%). On the other hand, it was found that the best percentage of nano-Al2O3 as a partial replacement of cement is 1.5%.